The Bakke Problem—Allocation of Scarce Resources in Education and Other Areas - Erwin N. Griswold (Washington University Law Quarterly, 1979)
Much has been written about the Bakke case, both before and since the Court's pronouncement. I do not propose to review these writings, or even to examine the opinions of the Court in any detail. It is enough, and fortunate, I think, that we are able to continue the essentially social process of experimentation in this area, knowing that race may be taken into account in academic admissions, but that quotas based on a two-track system are invalid.
Keywords: Colleges and universities; Race discrimination; Affirmative action